"Just-in-Place" labor: Driver organizing in the Uber workplace. (March 2021) - Wells, Katie J; Attoh, Kafui; Cullen, Declan
This paper examines the socio-spatial dynamics of worker agency in the platform economy in the Washington, D.C. region. Drawing on the field of labor geography, we document the collective and inherently spatial conditions of laboring under and through new technologies for three years prior to, and six months after, a strike by Uber drivers in May 2019. In doing so, we explore what Uber's platform means for the production, accumulation, and contestation of power. We argue that the big innovation of this platform is the creation of a "just-in-place" worker. Akin to those materials for assembly lines that arrived just-in-time for production, so too do drivers end up in just the right place for Uber's services to be offered. We also argue that Uber's attempts to keep its workers "just-in-place, " which generally isolate and disempower drivers, can actually enable new modes of organization. At a D.C. airport, drivers who were emplaced in a parking lot overcame one of the fundamental conditions of the Uber workplace: socio-spatial atomization. The airport became a space in which the "just-in-place" worker could, at least for a time, challenge such emplacement and exercise a form of collective worker agency by re-working Uber's dynamic pricing system.